Corporate Governance Approaches and Jordanian Companies Law - Abu Karky, Hetham; AlHdaithat, Hussien (DIRASAT: SHARI'A AND LAW SCIENCES, 2019)
There are two major approaches towards the realization of corporate governance: The institutional approach, and the legal approach. The choice of the appropriate approach towards corporate governance is a logical consequence of the development of economic impact factors.There are no official regulations regulating the corporate governance in Jordan yet, however, the Jordanian Companies Law considers some of the Corporate governance principles in it is articles.The objective of the article is to analyze the corporate governance methods to find out which of them could be applicable to Jordan. This could be achieved by giving an idea about the institutional and legal approaches and then, analyze the base of Corporate Governance at the Jordanian Companies law.